Multifunctional Bookshelf Inspired by Petronas Twin Towers - Abdul Halip, Juliana (Research in Management of Technology and Business, 2022)
: Due to high amount of population, most of the people stayed in apartment or condominium always faced the problems of less space of storage for books or magazines. Therefore, the objectives of this study are to identify the design characteristics, to design and to develop a prototype of multifunctional bookshelf inspired by Petronas Twin Towers. A total of 60 respondents who live in apartment or condominium at Kuala Lumpur were participated in the design characteristics determination using a set of questionnaire.  Data obtained from the survey was applied for sketches, mock-up, technical drawing, and fabrication of the prototype. Findings revealed that respondents preferred a square multifunction bookshelf with 4 to 5 layers of shelf, 5 to 7 compartments, made from the wood-based panel and have wood colour with lock wheels. A total of 101 thumbnails, 15 ideations, and 3 idea developments were sketched and the final design was determined by the design survey. A prototype of multifunctional bookshelf made from oil palm trunk plywood and finished with Formica in the brown walnut pattern was successfully fabricated. The  multifunctional bookshelf could benefit family who stay in apartment or condominium for storing books and magazines.